COVID-19-Related Mental Health Burdens: Impact of Educational Level and Relationship Status Among Low-Income Earners of Western Uganda - Lemuel, Ann Monima; Usman, Ibe Michael; Keneth Iceland, Kasozi; Alghamdi, Saad; Aigbogun, Eric Osamudiamwen; Archibong, Victor; Ssebuufu, Robinson; Kabanyoro, Annet; Iﬁe, Josiah Eseoghene; Swase, Dominic Terkimbi; Ssempijja, Fred; Ayuba, John Tabakwot; et al. (Kabale University, 2023)
Objective: The study aimed to investigate the relationship between mental health with the level of education, relationship status, and awareness on mental health among low-income earners in Western Uganda. Methods: This was a cross-sectional descriptive study carried out among 253 participants. Anxiety, anger, and depression were assessed using a modiﬁed generalized anxiety disorder (GAD-7), Spielberger’s State-Trait Anger Expression Inventory-2, and Beck Depression Inventory item tools, respectively. Results: The majority of our respondents were male (n = 150/253, 59.3), had a secondary level of education (104/253, 41.1), and were single (137/253, 54.2). No formal education and primary education (r2 = 47.4% and 6.4%, respectively) had a negative correlation with awareness of mental health care. In addition, no formal education had a positive correlation with anger and depression (r2 = 1.9% and 0.3%, respectively). Singleness in this study had a negative correlation with awareness of mental health care, anger, and depression (r2 = 1.9, 0.8, and 0.3%, respectively), and a positive correlation with anxiety (r2 = 3.9%). Conclusion: It is evident that education and relationship status inﬂuenced awareness on mental health care and mental health state among low-income earners in Western Uganda during the ﬁrst COVID-19 lockdown. Therefore, policymakers should strengthen social transformation through the proper engagement of low-income earners in this COVID-19 era. Keywords: Mental Healthcare, Awareness, Relationship, Status, Educational Level, COVID-19, Low-Income Earners, Western Uganda.